Inventory Control: Process management using the Kanban tool supported by the Scrum methodology (Research, Society and Development, 2019)
This article aims to use the Kanban system to analyze the organization in the inventory process, which aims to speed the process by reducing the loss of time and the delay in the demands. the possibility of integrating the agile Scrum to Kanban system was evaluated, in order to address the failures resulting from conventional Kanban for inventory management. The materials and methods used leave the realization of a proposal made to a franchise in the food industry with a qualitative assessment can identify the real problems, focusing on stock environment.